2022
DOI: 10.1021/acs.cgd.2c01147
|View full text |Cite
|
Sign up to set email alerts
|

trans-9,10-Dihydro-9,10-ethanoanthracene-11,12-dicarboxylic Acid: Remarkable Host Selectivities in the Presence of Mixtures of Anisole and Bromoanisole Isomers

Abstract: In this work,, a host compound that formed complexes with anisole (ANI), 2-bromoanisole (2-BA), and 4-bromoanisole (4-BA), was revealed to possess a remarkable affinity (93.1−98.6%) for 4-BA when recrystallized from any mixtures containing this guest species, be these binary (ANI/4-BA, 2-BA/4-BA, or 3-BA/4-BA), ternary (ANI/2-BA/4-BA, ANI/3-BA/4-BA, or 2-BA/3-BA/4-BA), or quaternary (ANI/2-BA/3-BA/4-BA) in nature. Furthermore, this striking host selectivity persisted even in binary solutions containing low con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The characteristics of the 2­( DED )·3­(ANI) complex have already been reported, and ANI was shown to occupy wide open and multidirectional channels and, as a result, the thermal stability of this complex was described as low; thermal experiments suggested that some of the guest species present were released from the crystals of the complex even at ambient conditions. In that work, which employed ANI and the bromoanisole isomers in mixtures, ANI was also shown to be a disfavored guest, as is the case in the present investigation.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…The characteristics of the 2­( DED )·3­(ANI) complex have already been reported, and ANI was shown to occupy wide open and multidirectional channels and, as a result, the thermal stability of this complex was described as low; thermal experiments suggested that some of the guest species present were released from the crystals of the complex even at ambient conditions. In that work, which employed ANI and the bromoanisole isomers in mixtures, ANI was also shown to be a disfavored guest, as is the case in the present investigation.…”
Section: Resultsmentioning
confidence: 90%
“…2-MA and 3-MA commenced escape from the crystals at 90.4 and 85.3 °C, respectively, while the complex containing ANI was unstable under ambient conditions. 31 Expected and measured mass losses corresponded (17.2 compared with 17.0, 17.2, and 17.4% for 2(DED)•2-MA, 2(DED)•3-MA, and 2(DED)•4-MA, respectively) with the exception of the unstable ANIcontaining complex. Finally, the guest release event was followed in each case by the host melt (240.7−243.8 °C) and, finally, its decomposition.…”
Section: Assessment Of the Selectivity Behavior Of Ded In Binary Solu...mentioning
confidence: 82%
See 3 more Smart Citations